KAJIAN TEKNIS TERHADAP STRUKTUR BANGUNAN DAN KELAYAKAN BANGUNAN MASJID NURUL IMAN KELURAHAN BALAM SEMPURNA KECAMATAN BALAI JAYA DAN MUSHOLLA AL-FALLAH KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Sugeng Wiyono; Anas Rizal; Billy Fredyanto (Yayasan Nusantara Hasana Berdikari, 2025)
This study contains the basis of the work, the results of the assessment and recommendations on the feasibility of the building structure of the Nurul Iman Mosque in Balam Sempurna Village, Balai Jaya District and the Al-Fallah Prayer Room in Bangko District, Rokan Hilir Regency. The implementation of this activity consists of checking the structural strength from the results of the quality test of the work results, which is based on the implementation of joint field surveys and direct quality inspection of the work results at the Laboratory of the Islamic University of Riau.